The effectiveness of Cognitive-behavioral therapy on self-harming thoughts and psychological well-being in students’ dissolution of romantic relationships - Rajabi Vandechali, Ali; Hasanzadeh, Ramezan; Abbasi, Ghodratollah (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of CBT on self-harming thoughts and psychological well-being in students with dissolved romantic relationships. Methods: This was a quasi-experimental study with pre-test and post-test design and follow-up with two experimental and control groups. The statistical population consisted of 587 patients referred to the counseling center of Sari city, from which 60 students with dissolved romantic relationships were selected based on the inclusion and exclusion criteria. Participants completed the Sanson & Sanson (2010) Self-Damage Questionnaire and the Ryff Psychological Well-Being Questionnaire (1989) in three pre-test, post-test, and follow-up sessions. The experimental group received 8 sessions of Cognitive-behavioral therapy and the control group did not receive any intervention. Data were analyzed using repeated measures analysis method with SPSS.22 software. Results: In the experimental group, the mean (standard deviation) of self-harming thoughts decreased from 18.53 (1.95) in the pre-test to 8.00 (1.64) in the post-test, but in the control group the mean (deviation) The criterion was self-injurious thoughts in the pre-test of 18.80 (2.07) and in the post-test of 18.93 (1.53), which did not differ. Also, in the experimental group, the mean (standard deviation) of psychological well-being in the pre-test was 43.60 (12.45) which increased to 97.13 (8.14) in the post-test, but in the control group, the average (standard deviation) of well-being Psychology was obtained in the pre-test of 40.80 (11.26) and in the post-test of 40.80 (11.30) which was not different. Conclusion: The study showed that positive treatment reduced self-harming thoughts and suicidal thoughts and increased psychological well-being in students with dissolved romantic relationships.